The Influence of Co-Branding Strategy On Purchasing Decisions With Brand Trust As a Moderating Variable - Eri Mardiani; Januar Kulsaputro; Yosef Tonce; Ekea Multi Febriyanti; Erina Alimin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Researchers believe that the combination of two brands will make consumers more interested in the products offered and will ultimately decide to make a purchase kuantitatif. Therefore, this research aims to analyze the influence of CO-Branding strategies on Purchasing Decisions. Different from previous studies, this research adds the Brand Trust variable as a moderating variable. This research is quantitative research with an explanatory approach, namely research that uses a number of previous studies as a reference and basis by analyzing them more deeply until finding new novel elements. The main data used in this research is primary data that researchers obtained from credible and accountable respondents in the form of Oke Oce employees and consumers spread throughout Indonesia. This data is classified as primary data which was distributed using a questionnaire method to 150 employees and 150 oke-oce consumers spread across Indonesia. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this research show the Co Branding Strategy variable can have a positive relationship and a significant influence on Purchasing Decisions because the T-Statistics value is above 1,960, namely 8,987 and the P-Values value is below The significance level is 0.05, namely 0.007. This is because the Co Branding Strategy can make consumers more interested, more curious, and ultimately consumers make purchasing decisions. In line with the results of the first line Path Coefficient, the results of the second hypothesis which the researcher believes can moderate the influence of the Dependent variable on the Independent variable in this study show similar results because the T-Statistics value is above 1,960, namely 14,540 and the P-Values value is below the level. significance is 0.05, namely 0.000. Thus, the first and second hypotheses in this research can be accepted and proven.